A comparative analysis of infraorbital foramen size in Paleogene euarchontans. Issue 105 (April 2017) - Muchlinski, Magdalena N.; Kirk, E. Christopher
Abstract: The size of the infraorbital foramen (IOF) is correlated with the size of the infraorbital nerve and number of mystacial vibrissae in mammals. Accordingly, IOF cross-sectional area has been used to infer both the rostral mechanoreceptive acuity and phylogenetic relationships of extinct crown primates and plesiadapiforms. Among living mammals, extant primates, scandentians, and dermopterans (Euarchonta) exhibit smaller IOF cross-sectional areas than most other mammals. Here we assess whether fossil adapoids, omomyoids, and plesiadapiforms show a reduction in relative IOF area similar to that characterizing extant euarchontans. The IOFs of 12 adapoid, 7 omomyoid, 15 plesiadapiform, and 3 fossil gliran species were measured and compared to a diverse extant mammalian sample. These data demonstrate that adapoids and omomyoids have IOFs that are similar in relative size to those of extant euarchontans. Conversely, IOFs of plesiadapiforms are on average about twice as large as those of extant euarchontans and are more comparable in size to those of extant non-euarchontan mammals. These results indicate that crown primates share a derived reduction in relative IOF size with treeshrews and colugos. Accordingly, a decreased reliance on the muzzle and an increased reliance on the hands for environmental exploration may have first evolved in the euarchontan stem lineage. However, the relatively large IOFs of plesiadapiforms imply a continued reliance on the muzzle for close exploration of objects. This finding may indicate that either parallel evolutionary decreases in IOF size occurred within Euarchonta or that plesiadapiforms lie outside the euarchontan crown group.